Assistance for Increasing Farmers' Capacity in Processing Coconut Fruit into Virgin Coconut Oil (VCO) in Emplak Village Kalipucang District Pangandaran Regency: Pendampingan Peningkatan Kapasitas Petani Dalam Pengolahan Buah Kelapa Menjadi Virgin Coconut Oil (VCO) Di Desa Emplak Kec. Kalipucang Kab. Pangandaran - Jenal Abidin; Asep Dudi Rianto; Aang Andi Kuswandi; Yayat Hidayat; Noer Ayunda Novalinda (Yayasan Ahmar Cendekia Indonesia, 2022)
Virgin coconut oil (VCO) is one of the processed products from coconuts that has high economic value. As one of the villages in Pangandaran Regency that produces a lot of coconut agricultural products, it is necessary to have a wider use of coconut itself. The benefit of community service from this program is to increase people's understanding, especially farmers or producers of virgin coconut oil (VCO). The goals to be achieved in processing coconuts into virgin coconut oil (VCO) are to increase the income obtained by the community because they have been able to process coconuts into virgin coconut oil (VCO), and to increase people's knowledge and skills in processing coconuts into virgin coconut oil (VCO). The training was held in February 2022 in Emplak Village, Kalipucang District, Pangandaran Regency. The implementation method used is divided into three stages, namely the coordination, preparation and training stages. The results of this community service have succeeded in training the community in Emplak Village to make virgin coconut oil (VCO) well. In addition, other results obtained from this service are high participant responses. This can be seen from their attendance and enthusiasm in participating in the training. The community has additional skills in utilizing and processing local natural resources (coconuts). Abstrak Minyak kelapa murni atau virgin coconut oil (VCO) adalah salah satu produk olahan dari buah kelapa yang memiliki nilai ekonomis yang tinggi. Sebagai salah satu desa di Kabupaten Pangandaran yang menghasilkan banyak hasil pertanian buah kelapa maka perlu adanya pemanfaatan lebih luas dari kelapa itu sendiri. Manfaat pengabdian masyarakat dari program ini adalah untuk meningkatkan pemahaman masyarakat, khususnya para petani atau penderes terhadap minyak kelapa murni “virgin coconut oil (VCO)”. Tujuan yang ingin dicapai dalam mengolah buah kelapa menjadi virgin coconut oil (VCO) adalah untuk mingkatkan pendapatan yang diperoleh masyarakat karena telah mampu mengolah buah kelapa menjadi virgin coconut oil (VCO), dan meningkatkan pengetahuan dan keterampilan masyarakat dalam mengolah buah kelapa menjadi virgin coconut oil (VCO). Pelatihan dilaksanakan pada bulan Februari 2022 di Desa Emplak, Kecamatan Kalipucang Kabupaten Pangandaran. Metode pelaksanaan yang digunakan dibagi dalam tiga tahap, yaitu tahap koordinasi, persiapan dan pelatihan. Hasil dari pengabdian masyarakat ini berhasil melatih masyarakat di Desa Emplak membuat virgin coconut oil (VCO) dengan baik. Selain itu hasil lainnya yang diperoleh dari pengabdian ini yaitu respon peserta tinggi. Hal ini dapat dilihat dari kehadiran dan antusias mereka dalam mengikuti pelatihan. Masyarakat memiliki keterampilan tambahan dalam memanfaatkan serta mengolah sumber daya alam lokal (buah kelapa).